2020
DOI: 10.1002/jcla.23104
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 and risk of atrial fibrillation: A systematic review and meta‐analysis

Abstract: Background Galectin‐3 is an inflammatory marker that is raised in myocardial fibrosis and inflammation. Recent studies have explored its role in predicting atrial fibrillation (AF) outcomes. The aim of this systematic review and meta‐analysis is to examine the association between serum concentration of galectin‐3 and AF. Methods PubMed, EMBASE, and the Cochrane Database were searched. A total of 280 studies were identified, of which 28 studies involving 10 830 patients were included in our meta‐analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
(134 reference statements)
1
16
0
2
Order By: Relevance
“…The largest meta-analysis, which included 28 studies and 10813 patients, was published in 2020. This meta-analysis demonstrated that galectin-3 is higher in patients with AF than in patients with sinus rhythm, and an increased level of galectin-3 is associated with a higher risk of AF development (OR = 1.45, 95% CI = 1.15–1.83, p = 0.002) [ 17 ]. However, for many years the role of galectin-3 in the development of AF in patients with MS remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The largest meta-analysis, which included 28 studies and 10813 patients, was published in 2020. This meta-analysis demonstrated that galectin-3 is higher in patients with AF than in patients with sinus rhythm, and an increased level of galectin-3 is associated with a higher risk of AF development (OR = 1.45, 95% CI = 1.15–1.83, p = 0.002) [ 17 ]. However, for many years the role of galectin-3 in the development of AF in patients with MS remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…isoprostanes, and others. [9][10][11][12][13][14] SND is associated with atrial fibrosis, atrial myopathy, and structural remodeling, creating a substrate that facilitates AF development and perpetuation. 3,4 Furthermore, bradycardia per se, ion-channel remodeling, abnormal calcium handling, electrophysiological alterations, and autonomic abnormalities contribute to the atrial arrhythmogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the role of pathophysiologic pathways that involve oxidative and inflammatory processes in AF is under meticulous investigation 9,10 . Several inflammatory indexes and oxidative stress markers have been associated with AF in different clinical settings 9‐14 . These include CRP, interleukin (IL)‐6, tumor necrosis factor (TNF), myeloperoxidase, galectin‐3, nitrotyrosine, F2 isoprostanes, and others 9‐14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations